2007
DOI: 10.1007/s00270-007-9226-z
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Chemoembolization of Unresectable Hepatocellular Carcinoma with Drug Eluting Beads: Results of an Open-Label Study of 62 Patients

Abstract: The purpose of this study was to assess the safety and efficacy of doxorubicin-loaded beads (DC Beads) delivered by transarterial embolization for the treatment of unresectable hepatocellular carcinoma (HCC). This open-label, single-center, single-arm study included 62 cirrhotic patients with documented single unresectable HCC. Mean tumor diameter was 5.6 cm (range, 3-9 cm) classified as Okuda stages 1 (n = 53) and 2 (n = 9). Patients received repeat embolizations with doxorubicin-loaded beads every 3 months (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
106
4
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(140 citation statements)
references
References 34 publications
21
106
4
9
Order By: Relevance
“…Patients with Child-Pugh classes A and B disease did not experience any major complications after treatment with DEB but did experience liver failure after treatment with conventional chemoembolization. Complication rates of our DEB group in Child-Pugh classes A and B mirror low complication rates reported by Varela et al [14] and Malagari et al [19]. Recent randomized multicenter study also showed improved…”
Section: Discussionmentioning
confidence: 50%
“…Patients with Child-Pugh classes A and B disease did not experience any major complications after treatment with DEB but did experience liver failure after treatment with conventional chemoembolization. Complication rates of our DEB group in Child-Pugh classes A and B mirror low complication rates reported by Varela et al [14] and Malagari et al [19]. Recent randomized multicenter study also showed improved…”
Section: Discussionmentioning
confidence: 50%
“…The appearance of drug-loaded microspheres has changed the nature and form of TACE (7,9). However, there is disparity in the development and use of those microspheres due to social and economic factors in various countries.…”
Section: Existing Problems and Prospects For The Futurementioning
confidence: 99%
“…The former consists of a biocompatible polymer such as polyvinyl alcohol hydrogel while the latter consists of a super-absorbent polymer. DC Beads (the brand name in Europe) were approved by the FDA under the name LC Beads (7,8). Hepasphere microspheres were approved by the European Union in 2004 and by the FDA in 2006.…”
Section: Drug-eluting Beads (Debs)mentioning
confidence: 99%
“…TACE was performed using a technique similar to that described in previous studies [1,2] . All patients were treated with subsegmental and/or segmental TACE.…”
Section: Tacementioning
confidence: 99%
“…One of the many evolving roles of contrast-enhanced ultrasonography (CEUS) in oncologic imaging is in the evaluation of the efficacy of transarterial chemoembolization (TACE) of liver tumors [1][2][3] . CEUS has been proved to be efficient in differentiating residual (enhancing) from necrotic (non-enhancing) tumor after TACE, and the therapeutic effect can be assessed by subjective, visual evaluation or by simple calculations (for example, by uni-or bi-dimensional measurements of the residual enhancing tumor at a representative section).…”
Section: Introductionmentioning
confidence: 99%